"Back into the Days of Slavery": Freedom, Citizenship, and the Black Family in the Reconstruction-Era Courtroom. (28th January 2019) - Perrone, Giuliana
Abstract : This article analyses domestic law cases brought by former slaves during the decade following the Civil War. It argues that ending slavery was a long and complex process that included not only granting rights to freedpeople, but also subtracting the incapacities previously imposed by bondage and applying certain rights retroactively. Reconstruction-era judges, throughout the era and across the South, overlooked the realities of slavery as a lived institution. Instead, they reimagined slavery as a collection of legal disabilities that could simply be subtracted and summarily resolved. This is how they would carry out abolition. The notion that slavery had to be undone stands in contrast to prevailing scholarship that emphasizes the acquisition and exercise of rights as demonstrative of consummate freedom. Instead, this article shows that even when positive law and judicial rulings were used to deconstruct the peculiar institution, slavery, as a legal construct, could not be fully demolished. Judges and freedpeople alike were left to face troubling legacies for which there was no remedy. No performance of legal acrobatics could alter, undo, or fully resolve the myriad ways slavery continued to affect many former slaves and influence the direction of their free lives. Abolition would remain incomplete.